Potensi Protein Reseptor Fertilisasi Zona Pelusida Kambing Sebagai Kandidat Imunokontrasepsi dengan Fertilisasi in vitro pada Sapi (POTENTIAL OF FERTILIZATION RECEPTOR PROTEIN GOAT ZONA PELLUCIDA AS CANDIDATE OF IMMUNOCONTRACEPTION BY USING IN VITRO FER - Mulyati, Sri; Mustofa, Imam; Mahaputra, Laba (Jurnal Veteriner, 2013)
Studies on the role of zona pellucida glycoprotein-3 (ZP3) in immunocontraception have been conductedin many species including goats (gZP3). Our previous study indicated that gZP3 effective in preventingpregnancy in mice. The aim of this study was to prove the evidence of cross reaction in gZP3 to preventfertilization in cow in vitro. Antibody of gZP3 was produced in mice. Immunized mice serum was analyzedusing ELISA technique and dot blot method. Sperm from frozen semen were processed then incubated incapacitation media supplemented with the gZP3, whilst the cow oocyte was incubated in maturationmedia supplemented with antibody of gZP3. Following this, the normal  in vitro fertilization (withoutincubation neither in gZP3 nor in gZP3 antibody) was performed, respectively. The results showed thatantibody titer of immunized mice serum was higher (p<0.05) than the control group. Dot blotting analysisshowed that the antibody of immunized mice were able to recognize gZP3 protein. The serum of immunizedmice which was supplemented in the maturation media of cow oocyte were able to decrease the cleavagerate (p<0.05). Protein gZP3 which was supplemented in the capacitation media of the sperm also coulddecrease the cleavage rate (p<0.05). It is concluded that goat-ZP3 protein may produce cross reaction incow.
Keywords: goat, zona pellucida-3, fertilization, cow